Evaluating 'natural resource curse' hypothesis under sustainable information technologies: A case study of Saudi Arabia. (October 2020) - Anser, Muhammad Khalid; Yousaf, Zahid; Nassani, Abdelmohsen A.; Vo, Xuan Vinh; Zaman, Khalid
Abstract: The role of Information and Communication Technologies (ICTs) in economic growth is widely documented in the scientific literature, while a relatively little attention is put on technology-embodied natural resource growth, energy demand and green development in the Kingdom of Saudi Arabia (KSA). This crucial issue needs fair assessment and analysis for country's long-term growth. The KSA's Vision -2030 of resource conservation agenda focuses on utilization of its precious natural resources, which are going to become scarce due to their higher marginal productivity that surpassing the marginal productivity of factor inputs in terms of labor wages and return on investment. The country values its ICTs infrastructure and motivated to build strong technology hub for reducing resource extraction costs and carbon abatement costs. In a given scenario, the study examined the technology-driven natural resource growth hypothesis under multifaceted factors, including carbon pricing, financial and trade liberalization policies, industrial value added, ores and metal exports, and population density. The study analyzed a time series data for a period of 1970–2018 for robust inferences. The results show that computer communications, telephone-mobile subscriptions, and technical cooperation grants promote country's total natural resource rents at the cost of higher energy demand, which increases carbon emissions. The per capita income and population density increases energy demand in the country. The study established an inverted U-shaped relationship between country's per capita income and fossil fuel combustion during the given time period. The efficient use of ICTs factors helpful to reduce carbon emissions and fossil fuel combustions in carbon pricing model. The natural gas rents do not support country's economic growth, which substantiate the 'resource curse' hypothesis, while oil rents and forest rents exhibit a positive impact on country's economic growth to support 'resource blessing' hypothesis. The inter-temporal setting shows that mineral rents will negatively influence country's economic growth over a time horizon. Thus, the technology-driven natural resource growth is vital to reduce natural resource prices and carbon abatement costs, which is the forefront challenge for policy makers in proposing long-term e-sustainable policies in a country. Graphical abstract: Image 1 Highlights: Technology driven natural resource growth hypothesis is evaluated in the context of KSA's economy. ICTs promote total natural resource rent on the cost of higher energy demand that increases CO2 emissions. The study verified inverted U-shaped EKC hypothesis for fossil fuel combustion in a country. ICTs infrastructure substantially decreases carbon-fossil emissions under carbon pricing model. Natural gas and mineral rents shows 'resource curse' while forest and oil rents support 'resource blessing' hypothesis.